BSRCA: Biological sequence analysis approach to robotic soccer with cellular automata classifier - P., Kiran Sree; I., Ramesh Babu; N.S.S.S.N, Usha Devi (2008)
This paper reports on the application of sequence analysis algorithms for agents in robotic soccer and a suitable representation is proposed to achieve this mapping.The objective of this research is to generate novel better in-game strategies with the aim of faster adaptation to the changing environment.A homogeneous non-communicating multi-agent architecture using the representation is presented.To achieve real-time learning during a game, a bucket brigade algorithm is used to reinforce Cellular Automata Based Classifier. A technique for selecting strategies based on sequence analysis is adopted.